Investigation On Physical, Mechanical And Thermal Properties Of Flexible Water-Based Epoxy Foam - Zainul, Zaiza (2006)
The effect of various blowing agent concentration and the water content on the physical, thermal and mechanical properties of flexible epoxy foam was investigated. The epoxy mixture was prepared by incorporation of p-toluene sulphonyl hydrazide (TSH) as blowing agent and polyamide as the epoxy curing agent, while the potassium hydroxide (KOH) was used at 3% as stabilizer. The mixing of the epoxy resin involved a use of Silverson homogenizer stirred at a rotor speed of 1500 rpm and a subsequent speed at 2000 rpm. Various foams were obtained by varying the foam formulation in the blowing agent composition range from 2 - 10 phr and the water content from 10% - 40% (w/w) at a constant level of epoxy to curing agent ratio, EP: PA (100:200). An investigation was performed on cell morphology, structure and cell size using scanning electron microscope (SEM) and the average cell size was measured using image analyser. Results indicate that the gelling time is significantly decreased with increasing water content but increases slightly with increasing blowing agent concentration. The gel content increases with increasing water content, which results in higher foam density. Blowing agent addition has shown to increase the average cell size, which significantly reduces the foam density. By contrast, the average cell size decreases with the increasing water content, and hence increases the foam density significantly. The reduction of compressive strength with the increase of blowing agent is attributed to the larger cell shape, size, and cell wall thickness and the decreased density of the foam, whereas the compressive strength increases with the increase of water content owing to smaller cell shape, size and thicker cell wall and the increased density of the foam. The compression set was observed to be density and temperature dependent.